Patent vitelline duct as a cause of acute abdomen: Case report of an adult patient - Arsenal SEZGİN and Bahri CAKABAY and Yasemin DOLEK and Sami AKBULUT and Feride ALEVLİ (Turkish Journal of Gastroenterology, 2019)
-